Examining and problematizing the journalistic discourses of radical rightism. Issue 1 (2nd January 2022) - Zhao, Steven
Abstract: This article examines the popular journalistic discourses on the terroristic actions and ideological beliefs of Brenton Tarrant as a way to illuminate the problematic ways in which the notions of radicalization and extremism of rightism are framed. I argue that the journalistic discourses implicitly frame radicalization and extremism as isolated standalone phenomena in terms of their ideas and ideological proponents. This framing is problematic because it stimulates a practical solution of suppression and a moral reaction of condemnation that serve to inadvertently fuel the growth of radicalization towards extremist attitudes and violence. Therefore, through my elaboration, I aim to lead the discussion towards a reframing of radicalization and extremism as not only standalone phenomena but also inherently interactive social processes. Such reframing carries important educational implications. I conclude that the educational role in the face of problematic discourses on radical rightism is to ensure that the classroom understands radicalization as a shared and interactive social process rather than as only an individual outcome. It is through such understanding that the educational approaches can then optimally resist radicalization and extremism through the acknowledgement of the social importance of inclusive dialogues.